2016
DOI: 10.4236/asm.2016.64006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bisphenol A on Testosterone Levels and Sexual Behaviors of Male Mice

Abstract: Objective: To evaluate the effects of bisphenol A (BPA) on testosterone levels and sexual behaviors of male mice. Methods: Forty 12-week-old male mice, 22 -25 g, were randomly allocated into four equal groups (n = 10 per group): the control group and three BPA exposure groups including low concentration group (10 mg/kg), middle concentration group (50 mg/kg) and high concentration group (100 mg/kg). Each mouse received BPA intraperitoneally injected for 21 consecutive days. Sexual behaviors and testosterone le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Endocrine disrupting chemicals are defined as any exogenous agents that can interfere with the synthesis, metabolism, and action of endogenous hormones (Phillips et al, 2008). Zang et al (2016) reported that BPA affects the functioning of the reproductive system and leads to infertility in male mice. The present study's results indicated that exposing rats to BPA caused a significant abnormality in their sexual hormone levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Endocrine disrupting chemicals are defined as any exogenous agents that can interfere with the synthesis, metabolism, and action of endogenous hormones (Phillips et al, 2008). Zang et al (2016) reported that BPA affects the functioning of the reproductive system and leads to infertility in male mice. The present study's results indicated that exposing rats to BPA caused a significant abnormality in their sexual hormone levels.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent work showed that BPA significantly reduced both SOD and CAT system activity as well as oxidised glutathione (H 2 O 2 ) generation and lipid peroxidation (Eid et al, 2015). More recently, the plasma testosterone levels and testis weight were found decreased by BPA in association with morphological alterations and changes in sperm count and motility (Zang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High concentration group more decrease in testes, epididymis and seminal vesicle weight. [64] 21 consecutive days Epididymis and seminal vesicle Serum and intratesticular testosterone levels were lowered.…”
Section: Testesmentioning
confidence: 99%
“…BPA at an extremely high dose (300 mg/kg) significantly increased serum thyroxine (T4) levels without changes in serum triiodothyronine (T3) and FSH levels [23]. BPA exposure was reported to decrease serum T levels in Swiss albino and C57BL/6 mice, but these doses varied between 0.5 μg/kg to 100 mg/kg [151, 152]. Additionally, Sadowski et al reported that Long-Evans rats exposed to low-dose BPA showed a decrease in FSH levels at weaning [65].…”
Section: Bpa Male Reproductive Toxicitiesmentioning
confidence: 99%